Nuclear Arms Control - Sauer, Tom. author. aut Link
XV, 146 p.
Keywords: The proliferation of nuclear weapons has been defined as the gravest potential threat to international peace and security. The concept of nuclear deterrence has to be revisited in this regard. The longer the Nuclear Weapon States hold on to their nuclear weapons, the bigger the chance that nuclear weapons will be spread and will be used (once again) by accident, in an authorized or unauthorized way, or that nuclear terrorism becomes reality. The marginalizing of nuclear weapons resulting in a Nuclear Weapon Free World should be considered as a viable alternative.